Implementation of Student Management in Improving Student Achievement at SMPN 3 Peterongan - Muhibbah, Aimmatul; Hanafi, Muhammad; Munawwaroh (ICONELT, 2024)
This research is motivated by the achievements achieved by SMPN 3 Peterongan Students who have increased, therefore the researcher wants to know implementation of student Management in improving student achievement at SMPN 3 Peterongan. This research uses Qualitative research methods. The data collection informants is the deputy head of student affairs. Data collection techniques using interviews, observation, and documentation. Research results: 1) Academic planning includes: planning, identifying student potential, Olympic programs and Coaching, planning facilities and infrastructure. Non-academic planning includes: planning and Identifying talents, interests, and potential of students socialization to students, development Of activities (extracurricular, life skills). 2) The implementation of student management in Improving student achievement is carried out by coordination between the head of School, Teachers of education personnel, and students. 3) Evaluation and improvement of achievement is done by comparing learning outcomes. This research has important significance in revealing the role of student management in improving academic and non-academic achievement at SMPN 3 Peterongan. The findings of this research can provide insights for the school in formulating more effective strategies to manage students’ potential, both in classroom learning activities and extracurricular activities. In addition, the results of this study are expected to be a reference for other schools in an effort to improve the quality of education through more planned and coordinated student management. Therefore, this research contributes to improving the overall quality of education and the formation of excellent student characters.